TEM and HRTEM Characterization of TiAl Diffusion Bonds Using Ni/Al Nanolayers. (29th August 2014) - Simões, Sónia; Viana, Filomena; Ramos, Ana S.; Vieira, Maria T.; Vieira, Manuel F.
Abstract: Diffusion bonding of TiAl alloys can be enhanced by the use of reactive nanolayer thin films as interlayers. Using these interlayers, it is possible to reduce the conventional bonding conditions (temperature, time, and pressure) and obtain sound and reliable joints. The microstructural characterization of the diffusion bond interfaces is a fundamental step toward understanding and identifying the bonding mechanisms and relating them to the strength of the joints. The interface of TiAl samples joined using Ni/Al nanolayers was characterized by transmission electron microscopy and scanning transmission electron microscopy. Microstructural characterization of the bond revealed that the interfaces consist of several thin layers of different composition and grain size (nanometric and micrometric). The bonding temperature (800, 900, or 1, 000°C) determines the grain size and thickness of the layers present at the interface. Phase identification by high-resolution transmission electron microscopy combined with fast Fourier transform and electron energy-loss spectroscopy analyses reveals the presence of several intermetallic compounds: AlTiNi, NiAl, and Al2 TiNi. For bonds produced at 800 and 900°C, nanometric grains of Ti were detected at the center of the interface.